Vaccination with nanoparticles combined with micro-adjuvants protects against cancer. Issue 1 (26th April 2019) - Mohsen, Mona O.; Heath, Matthew D.; Cabral-Miranda, Gustavo; Lipp, Cyrill; Zeltins, Andris; Sande, Marcos; Stein, Jens V.; Riether, Carsten; Roesti, Elisa; Zha, Lisha; Engeroff, Paul; El-Turabi, Aadil; et al.
Abstract : Background: Induction of strong T cell responses, in particular cytotoxic T cells, is a key for the generation of efficacious therapeutic cancer vaccines which yet, remains a major challenge for the vaccine developing world. Here we demonstrate that it is possible to harness the physiological properties of the lymphatic system to optimize the induction of a protective T cell response. Indeed, the lymphatic system sharply distinguishes between nanoscale and microscale particles. The former reaches the fenestrated lymphatic system via diffusion, while the latter either need to be transported by dendritic cells or form a local depot. Methods: Our previously developed cucumber-mosaic virus-derived nanoparticles termed (CuMVTT -VLPs) incorporating a universal Tetanus toxoid epitope TT830–843 were assessed for their draining kinetics using stereomicroscopic imaging. A nano-vaccine has been generated by coupling p33 epitope as a model antigen to CuMVTT -VLPs using bio-orthogonal Cu-free click chemistry. The CuMVTT -p33 nano-sized vaccine has been next formulated with the micron-sized microcrystalline tyrosine (MCT) adjuvant and the formed depot effect was studied using confocal microscopy and trafficking experiments. The immunogenicity of the nanoparticles combined with the micron-sized adjuvant was next assessed in an aggressive transplanted murine melanoma model. The obtained results were compared to other commonly used adjuvants such as B type CpGs and Alum. Results: Our results showed that CuMVTT -VLPs can efficiently and rapidly drain into the lymphatic system due to their nano-size of ~ 30 nm. However, formulating the nanoparticles with the micron-sized MCT adjuvant of ~ 5 μM resulted in a local depot for the nanoparticles and a longer exposure time for the immune system. The preclinical nano-vaccine CuMVTT -p33 formulated with the micron-sized MCT adjuvant has enhanced the specific T cell response in the stringent B16F10p33 murine melanoma model. Furthermore, the micron-sized MCT adjuvant was as potent as B type CpGs and clearly superior to the commonly used Alum adjuvant when total CD8 +, specific p33 T cell response or tumour protection were assessed. Conclusion: The combination of nano- and micro-particles may optimally harness the physiological properties of the lymphatic system. Since the nanoparticles are well defined virus-like particles and the micron-sized adjuvant MCT has been used for decades in allergen-specific desensitization, this approach may readily be translated to the clinic.